2021
DOI: 10.1002/cite.202000192
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Time‐Dependent Wetting Behavior of Gas‐Diffusion Electrodes for Reactivity Determination

Abstract: Tin foil and SnOx/C gas‐diffusions electrodes (GDEs) were investigated via electrochemical impedance spectroscopy (EIS) to extract the differential double‐layer capacitance (Cdl) as a measure of the wetted surface area. Time‐dependent Cdl values revealed an immediate stationary wetting for tin foil electrodes while a distinct increase of Cdl – which becomes stationary with time – was observed for GDEs. The time‐dependent wetting behavior of the GDEs was substantiated by physical post‐mortem characterization. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Since flooding is widely believed to be triggered primarily by the massive formation of carbonate precipitates on-top, and within deeper layers of the GDE [7][8][9][10][11][12][13][14][15], the amount and distribution of carbonates -in case of CO 2 electrolysers operated with a KOH anolyte, these are typically potassium carbonates and bicarbonates-seem to be an important tracer of flooding within the threedimensional GDE structure.…”
Section: Introductionmentioning
confidence: 99%
“…Since flooding is widely believed to be triggered primarily by the massive formation of carbonate precipitates on-top, and within deeper layers of the GDE [7][8][9][10][11][12][13][14][15], the amount and distribution of carbonates -in case of CO 2 electrolysers operated with a KOH anolyte, these are typically potassium carbonates and bicarbonates-seem to be an important tracer of flooding within the threedimensional GDE structure.…”
Section: Introductionmentioning
confidence: 99%
“…[68] Based on the results of consecutive electrolytic experiments performed with argon and CO 2 (Figure S14, Supporting Information), we support the view that flooding is not initiated by the carbonate precipitation, being in contradiction to the interpretation presented by Leonard et al [68] In fact, the intrusion of the electrolyte to micropores may be triggered by electrowetting at extreme cathodic potentials (Figure 3). [30][31][32][33][34][35][36][37][38][39][40] It is important to note that the ex situ SEM/EDX analysis of GDE cross sections, as performed in this work (Figures 4,5), can visualize areas to which the electrolyte has permeated during the electrolysis but cannot distinguish whether solid precipitates are formed during or after the electrolysis. [69] The MPL of 36BB contains cracks in low abundance (Figure 2; Figure S2, Supporting Information) and has high internal porosity (Table 1).…”
Section: mentioning
confidence: 99%
“…These opposing observations have been validated with oxygen reduction reaction, which provides information about the mass transport of gaseous reactants. , The reason behind the contradiction is still unclear, though we believe it could be attributed to the use of different GDE substrates: PTFE GDE vs carbon GDE. For example, for the benefits of Nafion to take effect, the ionomer–catalyst layer could require a direct contact with the gas–liquid interface, which may be a challenge in carbon GDEs . Recently, Bell and co-workers proposed a bilayer coating of cation- and anion-conducting ionomers on Cu to regulate the microenvironment, i.e., local concentration of OH – , H 2 O, and CO 2 , to favor the production of multicarbon molecules .…”
Section: Pitfallsmentioning
confidence: 99%
“…The crossover of gas products to the catholyte is also a concern for the accurate quantification of products as discussed previously. The extent of bubble formation can be further aggravated if the GDE is overly wetted or flooded, which pushes the gas–electrolyte interface further away from the catalyst layer (>10 μm). , Additionally, the crossover of gas reactant and products will be intensified if the pressure at the gas chamber is higher than that in the catholyte chamber. For example, Legrand et al reported that in their specified electrolyzer system, a pressure difference of more than 5 kPa would result in the undesired crossovers and thus formation of bubbles in the catholyte chambers .…”
Section: Pitfallsmentioning
confidence: 99%
See 1 more Smart Citation